2015
DOI: 10.5539/jfr.v4n2p92
|View full text |Cite
|
Sign up to set email alerts
|

Banana Vinegars Production Using Thermotolerant Acetobacter pasteurianus Isolated From Ivorian Palm Wine

Abstract: <p>Vinegar or sour wine is a product of alcoholic and subsequent acetous fermentation of sugary precursors. Among acetic acid producing bacteria, only few genera (<em>Acetobacter and Gluconobacter</em>) are used in vinegar industry. In this paper, we intended to produce vinegar at 37 °C using two <em>Acetobacter</em> <em>pasteurianus</em> strains (S3 and S32). These species were isolated from palm (<em>Elaeis guineensis</em>) wine and presented potentialiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Maximum concentration of ethanol was obtained in 72 hours and was of 7% (g/l). This concentration was higher than those values which was 6.4 g/l [19] but lower than other values which was 8.9 g/l and 22.4 g/l [14] [20]. This variability production of alcohol could be due to the metabolic capacity of yeasts or the adaptability of yeasts with various sugar concentrations during fermentation [20] [21].…”
Section: Alcoholic Content Of Vinegarmentioning
confidence: 81%
See 1 more Smart Citation
“…Maximum concentration of ethanol was obtained in 72 hours and was of 7% (g/l). This concentration was higher than those values which was 6.4 g/l [19] but lower than other values which was 8.9 g/l and 22.4 g/l [14] [20]. This variability production of alcohol could be due to the metabolic capacity of yeasts or the adaptability of yeasts with various sugar concentrations during fermentation [20] [21].…”
Section: Alcoholic Content Of Vinegarmentioning
confidence: 81%
“…In Côte d'Ivoire, an acidity content of 6% (w/w) was obtained during production of banana vinegar [19]. This difference between values could depend on the capacity of strains.…”
Section: Acetic Acid Content Of Vinegarmentioning
confidence: 99%
“…According to Ould El Hadj and others [43], excessive alcohol content can inhibit yeast growth. It was reported that 2% of alcohol weakens the growth of yeasts and 6% stops the multiplication of cells, during the first days of fermentation [44]. Absence of fecal coliforms in the yellow wine might be an indication of a good sanitary quality of the beverage.…”
Section: Discussionmentioning
confidence: 97%
“…Both yeast and AAB inoculums were prepared as described by Konate et al [18] with some modifications. Yeast inoculum was prepared by incubating 0.5 g of yeast powder in 100 ml of 10% sucrose (w/v) solution for 1 h at 30°C, and 20 ml of the yeast inoculum was added to inoculate 1 l of tomato juice.…”
Section: Preparation Of the Inoculum Of Yeast And Acetic Acidmentioning
confidence: 99%